2021
DOI: 10.3906/elk-2006-91
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling and study on noise characteristics of rotor eccentric SPMSM with unequal magnetic poles structure

Abstract: The establishment of the analytical model of the rotor eccentric surface-mounted permanent magnet synchronous motor (SPMSM) with unequal magnetic poles structure will be beneficial to calculating the magnetic field and studying noise characteristics quickly. Based on the equivalent surface current (ESC) method and equivalent boundary method, the analytical model of the rotor eccentric SPMSM with unequal magnetic poles structure is proposed. During the modeling process, the magnetic field produced by a permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In general, several indexes are often considered, i.e., the torque, vibration, and noise characteristics, during the process of motor optimization design. Some studies indicated that the SMPMM-UEPMS has a smaller torque ripple than the SMPMM-EPMS, yet it brought more complexity to the characteristics of the noise or the vibration [17]. Overall, the magnetic flux density of the SMPMM-UEPMS should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In general, several indexes are often considered, i.e., the torque, vibration, and noise characteristics, during the process of motor optimization design. Some studies indicated that the SMPMM-UEPMS has a smaller torque ripple than the SMPMM-EPMS, yet it brought more complexity to the characteristics of the noise or the vibration [17]. Overall, the magnetic flux density of the SMPMM-UEPMS should be investigated.…”
Section: Introductionmentioning
confidence: 99%